Anticipatory Accounts - Murphy, Elizabeth (University of California Press, 2004)
C. Wright Mills called for a truly sociological analysis of actors’ “motive talk,” which decouples the commonsense link between the reasons actors give for their actions and their mental state prior to those actions. Subsequent theoretical and empirical work has focused almost entirely on actors’ retrospective accounting for untoward conduct that has already taken place. The other aspect of Mills’s program, the reasons actors give for potentially untoward future conduct and in particular the empirical investigation of the link between the availability of an acceptable vocabulary of motives for anticipated conduct and the eventual enactment of that conduct, has been largely ignored. This article seeks to rehabilitate these lost dimensions using data from a longitudinal study of mothers’ infant feeding choices and practices. It examines how mothers account, in advance, for the possibility that they may eventually feed their babies in ways they consider suboptimal. Thirty of the thirty-six women interviewed indicated that they intended to breastfeed, emphasizing the benefits of this practice to their babies. However, seventeen of these women also anticipated that they might abandon breastfeeding and presented elaborate accounts of the motives that could lead them to do so. The findings support Mills’s claim that the availability of an acceptable vocabulary of motives for untoward conduct increases the probability that one will engage in such conduct. Mothers who had offered elaborate anticipatory accounts for abandoning breastfeeding were much more likely to do so than those who did not offer such accounts.